Impact of toxic metal pollution on surface water pollution: a case study of Tohma stream in Sivas, Turkey - Turhan, Ş.; Duran, C.; Kurnaz, A.; Hançerlioğulları, A.; Metin, O.; Altıkulaç, A. (Informa UK Limited, 2021)
This study was executed to investigate the acidification and heavy metal (Cr, Mn, Fe, Ni, Cu, Zn, and Pb) pollution of Tohma stream flowing near Kangal lignite-fired thermal power plant located in ...
Keywords: 13. Climate action; 6. Clean water